Electrochemical Microsensors: Phase‐Regulated Sensing Mechanism of MoS2 Based Nanohybrids toward Point‐of‐Care Prostate Cancer Diagnosis (Small 18/2020). Issue 18 (7th May 2020) - Ying, Zi; Feng, Lingyan; Ji, Dongqing; Zhang, Yuan; Chen, Wei; Dai, Yifan; Janyasupab, Metini; Li, Xinxin; Wen, Weijia; Liu, Chung‐Chiun
Abstract : In article number 2000307, Yuan Zhang and co‐workers present a self‐organized nanohybrid consisting of metal nanopillars in a semiconducting 2H‐MoS2 matrix for accurate analysis of prostate cancer biomarker, alpha‐methylacyl‐CoA racemase (AMACR) in complex human body fluids. The explored 2H‐MoS2 ‐based nanohybrid is employed for the fabrication of an electrochemical microsensor and is capable of effectively differentiating prostate cancer patients with healthy controls.